Evaluation of a prebiotic and potassium for the control of anthracnose in the tree tomato (2012)
Anthracnose is the most limiting disease in the production of the tree tomato; losses may exceed 50% if control measures are not appropriate. For this reason, farmers use continuous applications of fungicides. Prebiotics have been successfully tested in animals and humans in order to stimulate the growth of intestinal flora and fauna to improve digestion, achieve greater increases in weight, reduce infections and stimulate the immune system. In plants, there are no data on their effectiveness in disease control, for this reason, this research was conducted on the La Esmeralda farm located in the town of Silvana (Cundinamarca, Colombia); to evaluate the effect of a prebiotic (BioKakimu®) and potassium dose on disease control. We determined the incidence and severity of anthracnose, and crop production. We used a complete block design with three replications and twelve treatments, each experimental unit consisted of six plants, for a total of 216 plants and an area of 1,350 m2. The crop was 18-months-old and consisted of the common red variety. The results showed that the foliar incidence, severity and production had significant differences between the various treatments, where the prebiotic - K2O interaction showed favorable results for disease management in high doses of prebiotic (6 L ha-1).